Daily Functioning and Prefrontal Brain Morphology in Healthy and Depressed Community-Dwelling Elderly - Elderkin-Thompson, Virginia (2008)
OBJECTIVE: Self-perceived emotional vitality, intact mood, physical activity and social engagement are recognized as important indicators for lowered rates of morbidity and increased longevity in late-life, but little is known about their underlying neural substrates. This study examined relationships between self-reported levels of general functioning and the combined volume of three integrated prefrontal structures associated with self-perception and emotion. DESIGN: Cross-sectional SETTING: UCLA Semel Institute for Neuroscience, Los Angeles, CA PARTICIPANTS: Depressed (N=43) and comparison (N=41) elderly subjects. MEASUREMENTS: Magnetic resonance images of orbitofrontal, gyrus rectus and anterior cingulate gray and white matter volumes were corrected for intracranial volume and combined across structures to form white matter and gray matter scales. Subjects completed the RAND Short-Form 36 Questionnaire, a self-report evaluation of daily functioning. Subscales used for analysis were Physical Function, Energy, and General Health, which were not correlated with depression. RESULTS: White matter volumes were associated with self-perceptions of Energy for healthy as well as depressed individuals, and gray matter volume was associated with General Health. This latter association was strongest among patients with late-onset of depression, i.e., onset > age 50, although it appeared in all diagnostic groups. CONCLUSIONS: Although mild to moderate atrophy is expected in late-life, prefrontal atrophy may represent changes to neuroanatomical substrates that qualitatively modulate self-perceptions of energy and general health for both depressed and non-depressed persons.